What People Leave Behind Marks, Traces, Footprints and their Relevance to Knowledge Society - Comunello, Francesca; Martire, Fabrizio; Sabetta, Lorenzo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book focuses on a particular but significant topic in the social sciences: the concepts of (3z(Bfootprint(3y (Band (3z(Btrace(3y(B. It associates these concepts with hotly debated topics such as surveillance capitalism and knowledge society. The editors and authors discuss the concept footprints and traces as unintended by-products of other (differently focused and oriented) actions that remain empirically imprinted in virtual and real spaces. The volume therefore opens new scenarios for social theory and applied social research in asking what the stakes, risks and potential of this approach are. It systematically raises and addresses these questions within a consistent framework, bringing together a heterogeneous group of international social scientists. Given the multifaceted objectives involved in exploring footprints and traces, the volume discusses heuristic aspects and ethical dimensions, scientific analyses and political considerations, empirical perspectives and theoretical foundations. At the same time, it brings together perspectives from cultural analysis and social theory, communication and Internet studies, big-data informed research and computational social science. This innovative volume is of interest to a broad interdisciplinary readership: sociologists, communication researchers, Internet scholars, anthropologists, cognitive and behavioral scientists, historians, and epistemologists, among others.s
Keywords: Knowledge, Sociology of; Internet -- Social aspects; Social sciences -- Philosophy; Ethnology; Communication; Knowledge, Theory of; Sociology of Knowledge and Discourse; Internet Studies; Social Theory; Sociocultural Anthropology; Media and Communication; Epistemology